Tontura em idosos : diagnóstico otoneurológico e interferência na qualidade de vida - Scherer, Sabrina (2010)
With aging it is common to appear of multiple otoneurologic symptoms in the form of dizziness, hearing loss and tinnitus. The dizziness is a very frequent complaint among the elderly, reaching 85% of those over 65 years old. The aim of this study was to verify the otoneurologic diagnosis of elderly patients with dizziness and quantify its interference in their quality of life. Fifty six elderly patients with dizziness, mean age of 71,2 ± 8,5 years, varying between 60 and 90 years took part in the present research. An audiological diagnostic battery including tonal-vocal- and impedance-audiometry, balance assessment, nystagmus, positional and positioning vertigo and vecto-electronystagmography were performed. A specific questionnaire for dizziness to assess the quality of life, the Dizziness Handicap Inventory (DHI), which evaluates the handicap effects provoked by this symptom, with a score ranging from 0 (best) to 100 (worst) was used. Twenty nine patients (51,8%) presented rotatory dizziness, 27 (48,2%) nonrotatory dizziness and 42 (75%) presented some hearing complaint. All patients referred vestibular symptoms, being the positional vertigo the most frequent one. The majority (69.6%) presented altered audiometry, having as the most prevalent alteration the precipitous neurosensorial hearing loss. The non-rotatory dizziness was statistically significant associated with altered audiometry. The vestibular complaints of positional dizziness and imbalance presented difference significantly statistically significant compared to DHI. The Computerized Vecto-electro-nystagmography was altered in 47 patients (83.9%) and it indicates peripheral vestibular disorder in all cases. In the postcaloric hyperreflexia was the most prevalent, present in 21 patients (37.5%) and the most frequent diagnosis was Deficient Peripheral Vestibular Syndrome to the Left, present in 15 patients (31,9%). In regards to quality of life, the functional aspect had the highest average score among the three evaluated aspects, and it showed a difference statistically significant between the functional and emotional aspects. Based on this study it is possible come up with the idea that elderly patients with dizziness have, in most cases, present alterations in audiometry and vecto-electro-nystagmography examinations which indicate disorder in the vestibular system and that they also present alteration in their quality of life with and average score of 51 in the DHI questionnaire